Microsoft Cybersecurity Architect (SC-100) Cert Prep: 3 Design Security for Infrastructure by Microsoft Press. - Press, Microsoft; Pluta, Charles (linkedin.com, 2023)
Prepare for the third domain of the Microsoft Cybersecurity Architect SC-100 certification exam. Demonstrate your ability to design security strategies for infrastructure.